(untitled) (Research, Society and Development, 2022)
Objective: To determine the incidence of the main risk factors and also the prevalence of non-carious cervical lesions (NCCL) in relation to sex and age. Methodology: The literature search was conducted using the keywords and MeSH terms “Tooth Cervix”, “Non carious cervical lesions” and “Tooth Wear”, in the MEDLINE databases via PubMed and Scopus. Observational studies were included, which aimed to assess the relationship between sex, age and risk factors with cervical injuries. In addition, only studies in English, from the last five years, in their full version, were selected. Literature reviews, clinical cases, studies that did not include the main observation, studies that deviated from the topic and in other languages were excluded from the research. Results: 441 articles were identified, of which 17 were selected. There was no significant percentage difference between males and females, with percentages of 49% and 51%, respectively. Regarding the prevalence associated with the age group, a higher incidence was observed in the population over 65 years of age (36%). Regarding risk factors, gastroesophageal reflux, parafunctional habits, occlusal disorders and brushing problems were reported, but the acidic diet was the most incident in the literature (in 76.4% of the selected articles). Conclusion: The prevalence of NCCL increases with age, however it does not depend on sex, with an acidic diet being considered a risk factor.